Kelimpahan dan Similaritas Gastropoda di Perairan Melasti dan Segara Samuh, Badung, Bali - Pradnyani, Gusti Ayu Manik; Arthana, I Wayan; Dewi, Ayu Putu Wiweka Krisna (Current Trends in Aquatic Science; Vol 1 No 1 (2018), 2018)
Melasti and Segara Samuh beach are located in Badung Regency. Melasti beach (station 1) has a water activity only used for swimming. Meanwhile, Segara Samuh beach (station 2) has been utilized for tourism, such as water sport, and fishing. The development of tourism in both stations is feared to affect the abundance of living biota existence in it. This study aims to identify the difference morphological characteristic and the abundance of gastropods, as well as the similarity between points by type of gastropods.  This research has been conducted on February-March 2018. This research also used descriptive quantitative method. It has been found that there were 33 species in two stations that have not much different morphological characteristic and there were 25 different spesies in two stations . Station 1 has value of  gastropod abundance which was on 66,8 ind/m 2 , while station 2 was only 36 ind/m 2 . In general, the high relation and shells diameter have positive values with the highest R 2 is 0,99. A high value of similarity was found on 6 points as the result to the abundance of Conus lividus existence at point 4 and 5 with 0,48 as the highest result of negative correlation analysis. The measurement of water quality parameter at station 1 has resulted as follow; pH 7,7–7,8, DO 5,3–5,6 mg/L, salinity 30,3–30,9 ppt, and temperature 28–28,1 0 C. Meanwhile at station 2, it was resulted with pH 7,7, DO 5,3–5,4 mg/L, salinity 30–30,8 ppt, and temperature 29,6-30 0 C. Water condition in two stations were still within the range of seawater quality standards for marine life.